The Effect of using hot seat strategy on the achievement and free discussion among second intermediate students in the English language. (مجلة دراسات وبحوث إعلامية, 2025)
The goal of this study is to investigate the influence of using hot seat strategy on the achievement and free discussion among second-intermediate students in the English language, The sample of the study had been randomly chosen which consisted of 32-second students who are divided into two groups, one of them represented the experimental group while the second is control group which was be thought by applying the traditional method. Two hypotheses were established to achieve the goal of the study, The first hypothesis was innovative and was tested affording to the hot seat strategy and achievement, the other was according to the hot seat strategy and free discussion. Two instruments were used to assess the achievement of second students achievement, and the other is a measure of the ability of free discussion. The study was partial to the middle pupils at Taglib Middle School in the scholastic semester 2021\2022. Current results revealed that there are statistically significant differences between the experimental group and control group in favor of the experimental group